Shifts in dominant tree species modulate phyllosphere microbial diversity and function in successional forests - Zi-wen Gao; Zheng-ning Xu; Yi-lin Li; Lin Chang; Ning Li; Yang-chun-zi Liao; Wen-jing Meng; Hui Sun; Lin Huang (BMC Microbiology)
Abstract Background Phyllosphere microbiome plays a crucial role in maintaining plant fitness. However, its response to changes in dominant tree species during forest succession still remains poorly understood. Methods In this study, microbial isolation and high-throughput sequencing techniques were used to analyze the community structure and diversity of phyllosphere microbes in pure Pinus massoniana forests, mixed P. massoniana and Liquidambar formosana forests, and pure L. formosana forests. Results The results showed that the isolation rates of key plant fungal pathogens varied significantly in phyllosphere across forest types. In pure pine forest, Fusarium was most prevalent in pine needles, while in the mixed forest, Alternaria was dominant. For Liquidambar leaves, Phyllosticta dominated in pure forests, while Colletotrichum was prevalent in the mixed forests. Alpha diversity analysis revealed that higher microbial richness and diversity in the mixed forest compared to the pure forest. The bacterial community structure in Liquidambar leaves differed between the pure forest and the mixed forest. Co-occurrence networks confirmed more complex and stable microbial compositions and interactions in the mixed forest. Bacterial communities in pine needles exhibited higher functional capacity for methanotrophy and nitrogen fixation in the mixed forests. Conclusions The results demonstrate that the mixed forests foster greater microbial diversity, complexity, and functional potential in the phyllosphere compared to the pure forests, highlighting the importance of forest composition in shaping phyllosphere microbial communities.